METODOLOGI Metodologi Istinbath Hukum Imam Asy-Syafi’i - Nur Khalifah; Miftakhul Rohman (SINDA: Comprehensive Journal of Islamic Social Studies, 2022)
Ijtihād is a thought process to find out the law of a problem based on the most appropriate argument. Correct ijtihad will be able to provide answers to the problems at hand. The basis of true ijtihād is the ability to explore the arguments from the Qur'an and hadith and then process them using qualified tools, supported by correct and consistent methodologies. These three components with the addition of the most important factor, namely the straightness of intentions and an objective view, will undoubtedly be able to produce legal certainty for the problems that are often asked by mankind. Understanding the correct methodology and applying it appropriately will be able to produce the legal provisions sought in the ijtihād process itself. In this article, we will discuss more specifically about one of the great madhhab imams, namely Al-Imam Muhammad bin Idris Asy-Syafi'i rahimahullahu or Imam Shafi'i. The main issues that will be discussed in this article are about the legal basis used by Imam Syafi'i in determining Islamic law and the development of Islamic law or the Shafi'i school. In addition to also reviewing the methodological framework, to deliver him as an absolute mujtahid, the founder of the basic methodology in Islam. Imam al-Syafi'i's ijtihād methods contained in the book of al-Risālah include: Returning all matters to the Qur'ān, hadith, ijmā', the words of friends (al-Āṡār) and qiyās, issuing laws by looking at the substance of a argument, issuing the law by looking at its 'illat and lowering the argument only on things that are visible, as for the essence, then return to Allah swt. Imam Ash-Shafi'i argues that the main basis in establishing the law is the Qur'an and the Sunnah. If not, then by relying on the Qur'an and Sunnah. If the chain of hadith is continued until the Messenger of Allah and the sanad is authentic, then that is what is desired. Ijma as a proof is stronger than khabar ahad. If a hadith contains more than one meaning, then the meaning that is dzahir is the main one. If the hadiths are of the same level, then the one that is more authentic is more important.